Taller Experieducativas para fortalecer la indagación en los estudiantes de 4 años de la Institución Educativa n° 1591. Trujillo, 2018 - Guadalupe Vega, Rubi (2019)
The purpose of this research work is to demonstrate that the application of the Experieducativas workshop strengthens the inquiry in 4-year-old children of I.E N ° 1591 "La Casa del Niño" Trujillo- 2018._x000D_ The research is a pre-experimental type since it is made up of a single experimental and control group composed of 24 students in section B._x000D_ The investigation started under the observation which was made in the 4-year classroom in the EI " La casa del Niño”, since the children did not have lessons that favored the inquiry therefore the critical thinking was scarce that is why, it was formulated as a general problem: How does the application of the Experieducativas workshop strengthen the inquiry in 4-year-old students of the educational institution N° 1591. Trujillo, 2018?_x000D_ Therefore, it was proposed as a general hypothesis: The experiential workshop strengthens the inquiry in 4-year-old students of the educational institution n ° 1591. Trujillo-2018._x000D_ Then the pre-test was applied, which resulted in a low level of 22 students, a medium level of 1 student and a high level of 1 student; After carrying out the proposed workshop, we applied the post test that reached a high level of 6 students, at the middle level 15 students and at the low level 3 students._x000D_ Therefore, we can say that the inquiry allows children to form reflective critical thoughts from their own experiences and experiments, where the teacher is an active participant in their learning by providing resources that allow them to obtain information in a relevant and meaningful way